Impurity Segregation and Nanoparticle Reorganization of Indium Doped MgO Cubes - Niedermaier, Matthias (ChemNanoMat, 2019)
Metal oxide nanocomposites are non‐equilibrium solids and promising precursors for functional materials. Annealing of such materials can provide control over impurity segregation and, depending on the level of consolidation, represents a versatile approach to engineer free surfaces, particle‐particle interfaces and grain boundaries. Starting with indium‐magnesium‐oxide nanoparticle powders obtained via injection of an indium organic precursor into the magnesium combustion flame and subsequent particle quenching in argon, we investigated the stability of the trivalent In(3+) ions in the host lattice of MgO nanoparticles by determining grain growth, morphology evolution and impurity segregation. The latter process is initiated by vacuum annealing at 873 K and can be tracked at 1173 K on a time scale of minutes. In the first instance the surface segregated indium wets the nanoparticle interfaces. After prolonged annealing indium evaporates and leaves the powder via the gas phase. Resulting MgO nanocubes are devoid of residual indium, regain their high morphological definition and show spectroscopic fingerprints (UV Diffuse Reflectance and Photoluminescence emission) that are characteristic of electronically unperturbed MgO cube corner and edge features. The results of this combined XRD, TEM, and spectroscopy study reveal the parameter window within which control over indium segregation is used to introduce a semiconducting metal oxide component into the intergranular region between insulating MgO nanograins.